Identification of the quorum sensing signal of the opportunistic pathogen inducing bleaching disease in the red macroalga Halymenia floresii holobiont. Issue 1 (31st December 2022) - A Abdul Malik, Shareen; Saha, Mahasweta; Taupin, Laure; Bedoux, Gilles; Bourgougnon, Nathalie; Robledo, Daniel
ABSTRACT: Seaweed surface provides a suitable substratum for the settlement of microorganisms (bacteria, viruses, and plankton). These microbial partners may have either beneficial or detrimental effects on the host since surface microbiota can act either as a protective layer to the macroalgae (symbiotic beneficial relations) or, under changing environmental conditions, the microbial equilibrium may shift to a detrimental, pathogenic state thus inducing diseases in the host. In commercial aquaculture, seaweed diseases feature a growing concern. Pathogenicity of microorganisms that infect algal hosts is closely related to the release of virulence factors and the formation of biofilms, both of which are regulated by Quorum Sensing (QS). The main focus of this study is to determine the pathogenicity of the surface-associated bacteria of Halymenia floresii, a carrageenophyte that originated from distinct habitats. Twenty-five bacterial species isolated from the surface of H. floresii were individually tested for tip bleaching assay to evaluate their potential pathogenicity. Ten isolates significantly reduced the risk of tip bleaching in H. floresii and were designated as "significantly non-pathogenic". Vibrio owensii was identified as a "significant pathogen" inducing bleaching disease in H. floresii . By using LC-MS, we here identified its HomoSerine Lactones (HSL) QS signal, as a C4-HSL (short-chain). This study thus suggests a possible involvement of QS signal (short-chain) in the disease-inducing bacterium from the aquaculture ponds (an integrated multitrophic aquaculture system). This study firstly reports on the surface-associated bacteria of a lambda-carrageenophyte. This study must contribute to the development of dedicated strategies for disease control based on HSL disruption in aquaculture.